Operational matrix approach for approximate solution of fractional model of Bloch equation, Operational matrix for solution of fractional model of Bloch equation - Singh H. (My University, 2025)
In present paper operational matrix of integration for Laguerre polynomial is used to solve fractional model of Bloch equation in nuclear magnetic resonance (NMR). The operational matrix converts the Bloch equation in a system of linear algebraic equations. Solving system we obtain the approximate solutions for fractional Bloch equation. Results are compared with existing methods and exact solution. Graphs are plotted for different fractional values of time derivatives. © 2016